To determine the equation of the reflection of the graph \( y = 3x \) in the x-axis, we need to reverse the sign of the \( y \) value. Reflecting a function in the x-axis means replacing \( y \) with \( -y \), leading to the new equation:
\[ -y = 3x \quad \Rightarrow \quad y = -3x \]
Thus, the equation of the reflection of \( y = 3x \) in the x-axis is:
\[ y = -3x \]
None of the provided responses exactly say \( y = -3x \), but \( y = - (3x) \) is equivalent to \( y = -3x\).
Hence, the correct response is:
y = −(3x).